The ocean carbon sink enhances countries' inclusive wealth and reduces the cost of national climate policies - Wilfried Rickels; Felix Meier; Sonja Peterson; Sina Rühland; Sneha Thube; Johannes Karstensen; Conny Posern; Claudia Wolff; Athanasios T. Vafeidis; Patricia Grasse; Martin Quaas (Communications Earth & Environment, 2024)
Improving our understanding of future ocean carbon uptake requires a nuanced understanding of the value of the annual ocean sink. Here, we combine an abatement cost-based approach and a climate damage-based approach to assess the value of the annual ocean sink. The former shows that the aggregate cost of national climate policies could increase by up to USD 80 billion if the ocean carbon sink weakens by 10 percent. As a complementary perspective, the damage-based approach shows that the annual ocean carbon sink contributes between USD 300 billion and USD 2,332 billion to countries' inclusive wealth. Despite the conceptual appeal of the damage-based approach for its potential insights into regional wealth redistribution, uncertainties in national social cost of carbon estimates make it less reliable than the abatement cost-based approach, which in turn provides more reliable estimates for a fiscal cost assessment of improved monitoring services of the ocean carbon sink.
Keywords: 330